FILSAFAT INTEGRITAS:: KONFIGURASI, SPEKTRUM, DAN DIMENSINYA DALAM PELAYANAN HAMBA TUHAN - Paparang, Stenly R. (Jurnal Teologi RAI, 2024)
Integrity is a subject of human life involved in acts of leadership in general, and acts of service in particular. In fact, the application of integrity does not always go smoothly. Two faces appear in a person: hypocritization and good work performances. Also the spread of various actions that are not in line with the Bible in the world of servant of God's ministry, is part of the fading of integrity. This study aims to present the strengthening of understanding of integrity through the discourse of integrity philosophy in three categories, namely: configuration, spectrum, and dimensions in the service of servants of God. The use of qualitative methods is carried out by combining data in various literatures to provide significant points in the three categories of integrity philosophy. The results showed that the philosophy of integrity presents the quality of understanding, knowledge, and strengthening of the configuration, spectrum, and dimensions of integrity. This research also contributes to Christians to endure the test and pass on integrity, thus having an impact on the pollination of the configuration, spectrum, and dimensions of integrity in the future.